Hypersensitivity to polyethylene glycol (PEG) - Czarnobilska, Maria; Bulanda, Małgorzata; Kurnik-Łucka, Magdalena; Gil, Krzysztof (Folia Medica Cracoviensia, 2021)
The need for mass population vaccination against Covid-19 poses a public health problem. Allergic symptoms occurring after the 1st dose of the vaccine may result in resignation from the admin-istration of the 2nd dose. However, the majority of patients with mild and/or non-immediate symptoms may be safely vaccinated. The only absolute contraindication to administration of the vaccine is an anaphylactic reaction to any of its ingredients. Polyethylene glycol (PEG), widely used as an excipient in various vaccines, is considered the primary cause of allergic reactions associated with administration of Comirnaty (Pfizer/BioNTech) and Covid-19 Vaccine (Moderna) vaccines. However, hypersensitivity to PEG reported to date seems very rare, considering its widespread use in multiple everyday products, including medicines and cosmetics. In the paper, current literature data describing mechanisms of hy-persensitivity reactions to PEG, their clinical symptoms and diagnostic capabilities are presented. Un-doubtedly, the issue of hypersensitivity to PEG warrants further research, while patients with the diagnosis require individual diagnostic and therapeutic approach.
Keywords: polyethylene glycol; PEG; hypersensitivity to PEG; Covid-19 vaccine